Impacts of Consumption of Ultra-Processed Foods on the Maternal-Child Health: A Systematic Review - Oliveira, Priscila Gomes de; Sousa, Juliana Morais de; Assunção, Débora Gabriela Fernandes; Araujo, Elias Kelvin Severiano de; Bezerra, Danielle Soares; Dametto, Juliana Fernandes dos Santos; Ribeiro, Karla Danielly da Silva (Frontiers in Nutrition, 2022)
Background and Aims: Changes in eating patterns have been leading to an increase in the consumption of ultra-processed foods (UPF), negatively impacting the quality of the diet and generating risk of harm to the health of the adult population, however, there is no systematized evidence of the impact of UPF in maternal-child health. Thus, in this study we aimed to evaluated the association between UPF consumption and health outcomes in the maternal-child population. Methods: Systematic review registered on the International Prospective Register of Systematic Reviews (PROSPERO) (CRD42021236633), conducted according to the PRISMA diagram in the following databases: PubMed, Medline, Scopus, Web of Science, Scielo and CAPES thesis and dissertation directory. We included original cross-sectional, case-control and cohort studies in any language. Eligibility criteria were a) food consumption assessment by the NOVA classification, b) health outcome (nutritional and diseases), and c) maternal-child population (pregnant, lactating women and infants/children). All data were analyzed and extracted to a spreadsheet structured by two independent reviewers. We evaluated the methodological quality of the studies included using the Newcastle-Otawa Scale and RoB 2. Results: Searches retrieved 7801 studies and 15 contemplated the eligibility criteria. Most studies included were cohort studies (n=8, 53%), had children as their population (n=9, 60%) and only one study evaluated UPF consumption in infants and lactating women. Panoramically, we observed that a higher participation of UPF in children’s diet has been associated with different maternal-child outcomes, such as increase of weight gain, adiposity measures, overweight, early weaning, lower diet quality, metabolic alterations, diseases, and consumption of plastic originated from packaging. Only one of the studies included did not present high methodological quality. Conclusion: Despite the limited literature on UPF consumption and health outcomes in the maternal-child population, the highest UPF consumption negatively impacted nutrition and disease development indicators in pregnant, lactating women and children. Considering the expressive participation of these foods in the diet, other studies should be conducted to further investigate the impact of UPF consumption on different health indicators, especially in the lactation phase for this was the one to present the most important knowledge gap.